Estimation of antibody titres in sheep immunized with capsular serogroup B Pasteurella multocida oil adjuvant vaccine - Zihadi, Md Asief Hossain; Udoy, S M Ahsanul Kabir; Akther, Sonia; Rahman, Md Zillur (Bangladesh Journal of Infectious Diseases, 2024)
Background: Pneumonic pasteurellosis in sheep is an important economical disease in Bangladesh where Pasteurella multocida killed vaccine is prescribed as a preventive measure. Objective: The present research was conducted in 20 non-descript native sheep to estimate antibody titre in response to haemorrhagic septicaemia oil adjuvant vaccine by Pasteurella multocida Indirect Antibody Enzyme Linked Immunosorbent Assay. Methodology: This animal study was performed during January to March 2024 at Bangladesh Livestock Research Institute, Savar, Dhaka, Bangladesh. Twenty non-descript native female lamb born to non-immunized mother aged 3 to 4 months was acclimatized for on station experiment. The blood was collected at up to 63 days with seven days’ interval post vaccination. The vaccine seed molecularly identified for capsular sero-grouping by Polymerase Chain Reaction. Results: The seed bacterium was Pasteurella multocida capsular serotype B. The vaccine generated statistically significant (p<0.05) increased level of antibody titer compared to control group from day 14 that peaked at 42 days and starts to decline after 49 days and onwards. The mean ± standard deviation of antibody titre of treatment group was 1.79±0.33. In Levene teat, there was no variance equality in the samples was found. Conclusion: The oil adjuvant Hemorrhagic Septicemia vaccine produced by Livestock Research Institute; Bangladesh contained killed Pasteurella multocida capsular serogroup B. It was found to generate statistically significant antibody response in vaccinated sheep that started to rise from day 14 and peaked at 42 days. After 49 days, it started its declining trend up to the study period (69 days). Investigation of the field isolates and their subsequent immunoinformatic study could generate better knowledge in designing more effective vaccine candidate that would give durable protection. Bangladesh Journal of Infectious Diseases, June 2024;11(1):3-8